Evaluation of Arterial Stiffness Parameters Measurement With Noninvasive Methods—A Systematic Review - Marta Maria Niwińska; Sławomir Chlabicz (Cardiology Research and Practice)
Conclusions: More research on a larger population should be performed in order to introduce noninvasive devices into daily medical practice.